Gebotskostenförderung in Windenergie-Auktionen - Wauer, Niels; Lehmann, Paul; Maurer, Hans-Christoph (Wirtschaftsdienst, 2023)
Germany faces the challenge of rapidly breaking free from its dependence on fossil fuels. This requires a comprehensive transformation of the energy system. Onshore wind energy is one of the most important generation sources that must be developed on a large scale in order to decarbonise the energy sector. While the expansion targets were raised significantly with the Renewable Energy Law (Erneuerbare-Energien-Gesetz) 2023, the actual deployment of onshore wind energy remains in crisis. To accelerate the expansion, much has been discussed about providing land and simplifying the approval process. However, this article emphasises that reimbursing bid preparation costs can also contribute to driving the expansion of onshore wind energy.
CRIS-Team Scopus Importer:2023-03-31